Ka istini o ženi - o porijeklu degradacije žena / Towards the Truth about Women - The Origin of Female Degradation - Ler-Sofronić, Nada (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
Objavljeno u: Pregled: časopis za društvena pitanja, br. 3, god. LXVII, 1977.